An identity construction perspective on careers of Swedish international itinerants - Malin Näsholm (Management Revue, 2009)
Considering international assignments as part of an individual's career, beyond the traditional expatriate assignment as employed and sent out by a company, this paper focuses on international itinerants. The purpose of this paper is to increase the understanding of individuals with multiple international work experiences, crossing the boundaries of a single employer, their experiences, identifications and identity construction. In the study an identity construction perspective is applied on four in-depth interviews with Swedish international itinerants. Categories of narratives are identified where the itinerants experience ambiguities and paradoxes in their identity construction, what they identify with and implications are discussed.
Keywords: 650; international assignments; international itinerants; identity construction; career; social identity